A Case of Alveolar Bleeding from Clotting Abnormality by Cefmetazole - Eri Nakano; Tsubasa Fukuoka; Nao Takeuchi; Tomoyuki Seki; Michihiro Tamai; Makoto Araki (Case Reports in Medicine)
Cephalosporins are one of the most commonly used first-line antibiotics. In this report, we describe the case of a patient who developed alveolar bleeding due to clotting abnormality following the use of cefmetazole, one of cephalosporins containing an N-methylthiotetrazole (NMTT) side chain. Compared to other antibiotics, cephalosporins with an NMTT side chain cause a higher degree of bleeding events. The bleeding tendency is caused by the depletion of vitamin K-dependent clotting factors via inhibition of the vitamin K epoxide reductase. This mechanism of action is the same as warfarin. Recent years have seen an increase in the number of patients using direct oral anticoagulants that do not require coagulation tests. As a consequence, there may be an increase in the number of bleeding events due to anticoagulant drugs and such antibiotics coprescription. Therefore, this case is an instructive lesson.